The prevalence of malocclusion and the need for orthodontic treatment among adolescents in the northern border region of Saudi Arabia: an epidemiological study - Ravi Kumar Gudipaneni; Raed F. Aldahmeshi; Santosh R. Patil; Mohammad Khursheed Alam (BMC, 2018)
Abstract Background To assess the prevalence of malocclusion and orthodontic treatment need among adolescents using the dental health component (DHC) of the index of orthodontic treatment need (IOTN). Methods A descriptive cross-sectional study was conducted among 500 (mean age 16.25 ± 1.09) adolescents randomly selected from the northern border region of Saudi Arabia (KSA). The northern border region is sub-divided into three governorates: Ar'ar (186), Rafha (142) and Turayf (172). The data were recorded in questionnaires to assess the prevalence of malocclusion and estimate of DHC of the IOTN index. Results The most common malocclusions in order of prevalence were Angle's Class I (52.8%), Angle's Class II (31.8%), Angle's Class III (15.4%), crowding (47.2%), excessive overjet (> 2 mm) (22.2%), reduced overjet (< 1 mm) (11.4%), excessive overbite (> 2 mm) (23.4%), reduced overbite (< 1 mm) (12.2%), anterior crossbite (4.8%), posterior crossbite (9.4%) and open bite (4.6%). The most common facial profiles determined in the sagittal plane, were the straight facial profile (49.2%), convex (42.6%) and concave (8.2%). The prevalence of Grade 1 and 2 DHC was 49.4%, Grade 3 was 29.6%, Grade 4 and 5 was 21%. The grades of DHC of IOTN index were as follows: 48.73% of males and 50.22% of females showed grades 1 and 2. Grade 3 was observed in 30.32% of males and 28.69% of females. Grades 4 and 5 were recorded in 20.93% of males and 21.07% of females. Conclusions The prevalence of malocclusion and orthodontic treatment need among the north border region of KSA is comparable with that of other regional studies.